Investigation of assertiveness of young wrestlers in terms of socio-demographical perspective - Tazegül, Ü. (European Journal of Physical Education and Sport Science, 2016)
The purpose of the present study is to determine assertiveness levels of young wrestlers in Ankara City in terms of socio demographical perspective. In this research, the Rathus Assertiveness Schedule was harnessed for data collection purpose. The research sampling is composed of 81 wrestlers from Ankara Seker, MTA and Tedas Sport Clubs. Whereas collected data was analyzed by the SPSS 20 software; normal distribution status of these data was examined through the "Kolmogorov-Smirnov" test; their homogeneity was examined through ''Anova-Homogeneity of Variance" test. As a result, it was determined that collected data was homogeny and normally distributed. In analysis of data, descriptive statistic and one-way Anova variance analysis for determining the difference among the two or more variables were applied. Finally, it was found that assertiveness score of sportsmen with 4-5 years of sport experience was greater than the sportsmen in other groups; assertiveness score of 17 years-old wrestlers was greater than the ones from other age groups.